A survey to assess the prevalence of Hepatitis B in the adult HIV positive population of the TC Newman ARV centre, Paarl - King, Jeanmari; Botha, Jeanmari (Stellenbosch : Stellenbosch University, 2015)
Thesis (MBchB)--Stellenbosch University, 2016